Developing Strategies to Improve Business Model of Online Laundry Marketplace Startup - Taqyya Naufinda Asnin; Yudha Prambudia; Rosad Ma'ali El Hadi (School of Industrial and System Engineering, Telkom University, 2021)
The Infineeds is a startup engaged in online laundry marketplace services for households. The current online marketplace business can be considered as a fairly competitive business, especially for Infineeds which is a new business or startup. Therefore, it is important for Infineeds to have a well-prepared sustainable business model. The Business Model Canvas was used to analyze Infineeds' business model. With a Strengths, Weaknesses, Opportunities, Threats analysis approach, alternative business development strategies are obtained that are in accordance with the company's internal and external environmental conditions. The weighting using Quantitative Strategic Planning Matrix is done to get alternative priorities for business development strategies. The priority alternatives are then included in the Business Model Canvas as a new component. The results of the analysis show that Infineeds is in a growth-oriented strategy position, which is to take advantage of internal strengths to take advantage of as many opportunities as possible with the highest alternative development strategy is the strategy to using Search Engine Optimization with Total Attractiveness Score is 6.62 as well as the development of a business model canvas on the components of channels, key activities, and key partners